2016
DOI: 10.3102/0162373716670260
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and Teaching Effects on Students’ Attitudes and Behaviors

Abstract: Research has focused predominantly on how teachers affect students’ achievement on tests despite evidence that a broad range of attitudes and behaviors are equally important to their long-term success. We find that upper-elementary teachers have large effects on self-reported measures of students’ self-efficacy in math, and happiness and behavior in class. Students’ attitudes and behaviors are predicted by teaching practices most proximal to these measures, including teachers’ emotional support and classroom o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
275
2
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(321 citation statements)
references
References 70 publications
22
275
2
22
Order By: Relevance
“…Effectiveness studies pay a lot of attention to classrooms since they are avenues where teacher attributes and student attributes interact. Therefore, quality teaching is the most important factor at the classroom level and thus teacher effectiveness in the classroom is one of the most significant factors related to student achievement (Blazar, 2016). …”
Section: Is Teacher Education Level and Experience Impetus For Studenmentioning
confidence: 99%
“…Effectiveness studies pay a lot of attention to classrooms since they are avenues where teacher attributes and student attributes interact. Therefore, quality teaching is the most important factor at the classroom level and thus teacher effectiveness in the classroom is one of the most significant factors related to student achievement (Blazar, 2016). …”
Section: Is Teacher Education Level and Experience Impetus For Studenmentioning
confidence: 99%
“…Moreover, teachers who have greater content knowledge tend to have a positive effect on students' subject-specific self-beliefs, such as their sense of mastery and self-efficacy (Blazar and Kraft, 2015). 5 …”
mentioning
confidence: 99%
“…Research has demonstrated that teacher effectiveness as measured by student academic achievement varies widely (e.g., Aaronson, Barrow, & Sander, 2007;Rockoff, 2004;Rowan, Correnti, & Miller, 2002) and that teachers improve at different rates (Atteberry, Loeb, & Wyckoff, 2013). A growing body of evidence also suggests teacher quality is an important contributor to student achievement (e.g., Blazar & Kraft, 2015;Chetty, Friedman, & Rockoff, 2014;Clotfelter, Ladd, & Vigor, 2007;Rivkin, Hanushek, & Kain, 2005). Specifically, the quality of teachers' instruction has been linked to student achievement outcomes (e.g., Allen et al, 2013;Gamoran, Porter, Smithson, & White, 1997;Wenglinsky, 2002;Westbury, 1993).…”
Section: Introductionmentioning
confidence: 99%